PENGEMBANGAN GAME EDUKASI DIGITAL DALAM MENINGKATKAN KEMAMPUAN MEMBACA AUD DI TK IT AL-HASANAH PRABUMULIH - Septaria, Lara; Leny Marlina; Kurnia Dewi; Faisal Abdullah; Lidia Oktamarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood reading skills at TK IT Al-Hasanah Prabumulih remain relatively low, particularly in recognizing letters, associating letters with their corresponding sounds, and comprehending simple words and sentences. This condition is primarily attributed to the continued use of conventional learning media, which are less engaging and fail to sufficiently motivate children to participate in the learning process. This study aimed to develop a valid, practical, and effective digital educational game to enhance early childhood reading skills. The research employed the Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The research participants were 15 children from Group B at TK IT Al-Hasanah Prabumulih. Data were collected through observations, interviews, questionnaires, and reading ability tests. The data were analyzed using validity, practicality, and effectiveness assessments, while effectiveness was further examined through a paired-samples t-test. The results indicated that the developed digital educational game was categorized as highly valid, with validation scores of 94% from the subject matter expert, 97% from the media expert, and 88% from the language expert, resulting in an average validity score of 94.16%. The practicality evaluation showed that the game was highly practical, receiving a teacher assessment score of 95.53%, while students' responses indicated that the game ranged from practical to highly practical. Furthermore, the effectiveness test demonstrated a significant improvement in children's reading achievement, with the average score increasing from 54.38% in the pre-test to 83.76% in the post-test. The paired-samples t-test also revealed a statistically significant difference (t = 8.787 > ttable = 2.160; p < 0.05). Therefore, the developed digital educational game is considered feasible and effective for improving early childhood reading skills.